OSSEOINTEGRATION OF THE INTRAMEDULLARY IMPLANT IN FRACTURE OF THE DIAPHYSIS OF A LONG BONE - A.V. Popkov (Journal of Global Pharma Technology, 2016)
In the experiment on dogs, nails coated with hydroxyapatite were introduced intramedullary in the tibia. By using light microscopy of histological sections and scanning electron microscopy, bone marrow space around the implant was studied. It was found that an area of active apposition bone formation is formed around the nails, and bone case is formed with the properties of osteogenesis conductor and inductor, providing directional growth of bone tissue and reparative bone formation. The extent of osseointegration of intraosseous implant was determined by separation method when removing intramedullary nail a month after the surgery. Active implant osseointegration provides guaranteed diaphysis fracture healing in 2-3 weeks. Keywords:  Intramedullary osteosynthesis, Hydroxyapatite coating, Reparative bone formation, Osseointegration.